The Effects of Peanuts and Tree Nuts on Lipid Profile in Type 2 Diabetic Patients: A Systematic Review and Meta-Analysis of Randomized, Controlled-Feeding Clinical Studies - Xia, Jia-yue; Yu, Jun-hui; Xu, Deng-feng; Yang, Chao; Xia, Hui; Sun, Gui-ju (Frontiers in Nutrition, 2021)
Background: Type 2 diabetes mellitus (T2DM) was found to be associated with metabolic disorders, particularly abnormal glucose and lipid metabolism. Dietary food choices may have profound effects on blood lipids. The primary objective of this study was to examine the effects of peanuts and tree nuts intake on lipid profile in patients with Type 2 diabetes. Methods: According to PRISMA guidelines, we performed a systematic search of randomized controlled clinical trials and systematic reviews published in PubMed, Web of Science, Embase, Scopus and Cochrane library, from inception through June 2021. Studies in populations with Type 2 diabetes, which compare nuts or peanuts to a controlled-diet group were included. We used the mean difference (MD) with 95% CIs to present estimates for continuous outcomes from individual studies. Additionally, we used the GRADEpro tool to evaluate the overall quality of evidence. Results: Sixteen studies involving 1041 participants were eligible for this review. The results showed that peanuts and tree nuts supplementation did not induce significant changes in LDL-C (mean difference=-0.11; 95% CI: -0.25 ~ 0.03, p=0.117) and HDL-C (mean difference=0.01; 95% CI: -0.01 ~ 0.04, p=0.400) in Type 2 diabetics patients. Additionally, we found that peanuts and tree nuts intake may cause a significantly reduction in TC (mean difference=-0.14; 95% CI: -0.26 ~ -0.02, p=0.024) and TG (mean difference=-0.10; 95% CI: -0.17 ~ -0.02, p=0.010). In the subgroup analysis, a significantly greater reduction in TC was observed in studies which duration was less than 12 weeks (mean difference=-0.22; 95% CI: -0.37 ~ -0.08, p=0.002). The quality of the body of evidence was ‘moderate’ for TC and TG, the quality of evidence for LDL-C and HDL-C were ‘low’. Conclusion: Our findings suggest that consuming peanuts and tree nuts might be beneficial to lower total cholesterol concentration and triglyceride concentration in type 2 diabetics subjects. Furthermore, peanuts and tree nuts supplementation could be considered as a part of healthy lifestyle in the management of blood lipids in type 2 diabetics patients. Given some limits observed in the current studies, more well-designed trials are still needed.